Metabolism of gallic acid and catechin by Lactobacillus hilgardii from wine - Alberto, Maria Rosa (2004)
The ability of Lactobacillus hilgardii 5w to metabolize gallic acid and catechin was evaluated. It was grown in a complex medium containing gallic acid or catechin. The metabolites were analyzed by high-performance liquid chromatography and identified by comparing the retention times and spectral data with the standards of a database. In gallic acid-grown cultures, gallic acid, pyrogallol, catechol, protocatechuic acid, p-hydroxybenzoic acid, p-hydroxybenzaldehyde, and p-hydroxybenzyl alcohol were detected. In catechin-grown cultures, catechin, gallic acid, pyrogallol, catechol, p-hydroxybenzoic acid, acetovanillone, and homovanillic acid were detected. This work presents evidence of gallic acid and catechin degradation by L. hilgardii from wine.